The Connection of the Existence of God with the Physics Phenomenon - Yulia Zahra (UIN Syarif Hidayatullah Jakarta, 2020)
AbstractOne of the best pieces of evidence of physics phenomenon which could give us the description of the existence of God is Dark Energy. Dark Energy is an unknown form of energy that affects the universe on the largest scales, but until now, scientists have not proven exactly where the dark matter came from. One of the religions that beliefs in God are Islam. In Islam, God is a matter which we could feel but could not see.Keywords: Dark Energy, The God, Islam